Profile Triglycerides Japanese Quail (Coturnix coturnix japonica) After Giving Turmeric (Curcuma longa) Powder - Sukarman Hadi jaya Putra; Tyas Rini Saraswati; Sri Isdadiyanto (Chemical Engineering Diponegoro University, 2015)
The purpose of this study was to determine the triglyceride profile of Japanese quail (Coturnix coturnix japonica) after being given the parameters of turmeric (Curcuma longa) powder; feed intake, profiles of liver triglycerides, profiles of serum triglycerides and profiles of meat triglycerides. This study uses an experimental method with A Completely Randomized Design Pattern. Test animals used were 45 female Japanese quails were divided into 3 groups, namely; P0: quail were not given turmeric powder, P1: quail were given turmeric powder a dose of 54 mg/quail/day, P3: quail were given turmeric powder a dose of 108 mg/quail/day. Each group with 5 replications. Each repeat consists of 3 Japanese quails. Provision of treatment every day for 30 days starting from the age of 14 days. Data were analyzed using analysis of variance (ANOVA) followed by Duncan's test with 95% confidence interval (α = 0.05 level). Analysis of the data used is software Minitab software 16. Results showed that the levels of turmeric powder are given in Japanese quail significant (P˂0.05) on liver triglyceride levels, serum and Japanese quail meat but had no significant effect (P˃0.05) on consumption feed. The results showed that the optimal dose of turmeric powder to lower triglyceride levels of Japanese quail is 108 mg/quail/day as evidenced by the highest decrease in liver triglyceride profiles, profiles of serum triglycerides and triglyceride profiles of Japanese quail meat compared with other treatments.